2018
DOI: 10.1002/awwa.1124
|View full text |Cite
|
Sign up to set email alerts
|

Smart Water Meters and Data Analytics Decrease Wasted Water Due to Leaks

Abstract: Advanced metering infrastructure (AMI) allows for hour-by-hour monitoring of water usage and has created new opportunities to communicate with customers. This article summarizes the results from a large-scale deployment of an AMI system with more than 85,000 residential customers. Households were provided with access to a secure customer online portal where they could view their consumption information, use a leak detection algorithm to monitor their consumption patterns, and set alerts when a potential leak w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Analysing the impact of customer access to an online portal by the City of Sacramento residents over an 18 month period, Schultz et al identified a 50% reduction in the occurrence of leaks (down from 12% to 6%) and a 34% reduction in the length of time to fix the leak [34].…”
Section: Enabler#4-establish a Detailed Customer Data Portal For Singmentioning
confidence: 99%
“…Analysing the impact of customer access to an online portal by the City of Sacramento residents over an 18 month period, Schultz et al identified a 50% reduction in the occurrence of leaks (down from 12% to 6%) and a 34% reduction in the length of time to fix the leak [34].…”
Section: Enabler#4-establish a Detailed Customer Data Portal For Singmentioning
confidence: 99%
“…Real-time leak detection and alerts can lead to prompt repairs of leaks, thereby saving a substantial amount of water. To accomplish this task, many approaches have been employed [72][73][74][75][76]. Among these approaches, clustering techniques is the most popular for leak detection, followed by the hybrid approach (Table 4).…”
Section: Leaksmentioning
confidence: 99%
“…Farah and Shahrour ( 2017 ) conducted a study, where an intelligent measurement system is implemented to detect possible leaks in a university campus, and it is proposed to combine the Water Balance rules with Minimum Night Flow (MNF), which results in 97% accuracy, thus, is achieved to reduce the waste of water by leakage. In the research article by Schultz et al ( 2018 ), a portal is implemented in a city of California where residents can monitor their water consumption; thus, for leak detection, it is proposed to establish based on an average (AVG) a limit (7.5 gph) of continuous water consumed during a 24-h period; likewise, its results show that users who used the system came to reduce by 50% the chances of having a leak again, but highlights that their methodology does not detect leaks less than the established limit. On the other hand, Farah and Shahrour ( 2018 ) demonstrated that using an automatic measurement system (AMR) for monitoring water been consumed, some water leakage can be detected quickly, for this they use a density probability function in order to identify regions of more or less probabilities of leakage based on data that was consumed before, during workdays, weekends, holidays, in this way, resulted they were able to detect 3 leaks in the Scientific Campus of the University of Lilledurante during 2015.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This generates a daily lack of knowledge of water consumption and the inability to detect in time a non-visible leak that results in a waste of this resource and economic losses even for the supplier when this resource is subsidized. An alternative to this problem is the use of smart systems that can save to generate water from 2.8 to 10.0% (Liu and Mukheibir 2018 ); this avoids wrong measurements generated by human error, and it creates the trust in consumers in terms of receipts and water consumption payments (Joo et al 2015 ), also it allows to report water leakage, which reduces the probability of reoccurrence by 50% (Schultz et al 2018 ). Currently, there are several smart measurement systems that also help detect, predict, and alert in time any leakage or excess of water.…”
Section: Introductionmentioning
confidence: 99%